Landmark Yiddish plays : a critical anthology - Berkowitz, Joel, 1965-; Dauber, Jeremy, 1973- (SUNY series in modern Jewish literature and culture., 2006)
"Offering snapshots of a pivotal era in which the Jews of Europe made the transition from a traditional to a more modern world, the Yiddish plays translated and collected here wrestle with issues that continue to concern us today: changing gender roles, generational conflict, class divisions, and religious persecution. In their introduction to the volume, Joel Berkowitz and Jeremy Dauber place the plays in the context of the development of modern drama and Yiddish drama and examine their treatment of social, political, and religious issues. The many ways in which the plays address these issues make them transcend their own time, exciting a new generation of readers and theatergoers."--Jacket.